Unexpected Signals in a System Subject to Kinetic Proofreading - Liu, Zhao-Jun; Haleem-Smith, Hana; Chen, Huaxian; Metzger, Henry (Proceedings of the National Academy of Sciences - PNAS, 2001)
When multivalent ligands attach to IgEs bound to the receptors with high affinity for IgE on mast cells, the receptors aggregate, tyrosines on the receptors become phosphorylated, and a variety of cellular responses are stimulated. Prior studies, confirmed here, demonstrated that the efficiency with which later events are generated from earlier ones is inversely related to the dissociation rate of the aggregating ligand. This finding suggests that the cellular responses are constrained by a "kinetic proofreading" regimen. We have now observed an apparent exception to this rule. Doses of the rapidly or slowly dissociating ligands that generated equivalent levels of tyrosine-phosphorylated receptors comparably stimulated a putatively distal event: transcription of the gene for monocyte chemoattractant protein 1. Possible explanations of this apparent anomaly were explored.